Assessment of conventional and microwave heating effects on the variation of the bioactive compounds of Chétoui VOO using HPLC-DAD-ESI-TOF-MS - Imen Oueslati; Amani Taamalli; Anis Loubiri; David Arráez-Román; Antonio Segura-Carretero; Mokhtar Zarrouk (Arabian Journal of Chemistry, 2020)
The goal of this work was to monitor the hydrophilic profile of the virgin olive oil (VOO) of the second main Tunisian variety, “Chétoui”, in order to achieve a better understanding of the behavior of the bioactive phenolic compounds during 0, 2, 5, 10, and 15 min of microwave heating at medium power 800 W, and 0, 2.5, and 5 h of conventional heating at 180 °C. The extent of the oxidative and hydrolytic degradation of the different phenolic subclasses was evaluated using high-performance liquid chromatography (HPLC) coupled to electrospray time-of-flight mass spectrometry (TOF-MS) method. During heating process, the most represented component in Chétoui VOO was found to be isomer 1 and 2 of deacetoxy oleuropein aglycone, and hydroxy decarboxy oleuropein aglycon. These compounds may be considered as direct markers for the degree of transformation of secoiridoids during heating process. Among the studied phenolic compounds, hydroxytyrosol, tyrosol, luteolin and apigenin displayed the highest heating resistance in the whole time range of microwave and conventional applications. However, the main secoiridoids quantified in the fresh VOO, isomer 2 of oleuropein aglycone, and ligstroside aglycone, decreased in concentration with the thermal treatment and this decrease was drastic under conventional heating. Keywords: Tunisian olive variety, Olive oil degradation, Thermo-oxidation, HPLC-ESI-TOF-MS, Phenolic compounds, Microwaves, Conventional oven